Investment policy review : Mozambique (UN New YorkUS, 2012)
Provides a comprehensive assessment of the regulatory framework for investment and identifies a number of key weaknesses, including in particular: (i) the general approach to investment rulemaking; (ii) corporate taxation and the structure of tax incentives; (iii) the employment of foreigners and access to skills; (iv) access to land; v) PPPs and the management of mega-projects; and (vi) licencing and inspections.
Keywords: INVESTMENT POLICY